Synthesis and properties of 6-(2,6-dichlorophenyl)-3-(3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-5H-[1,2,4]triazolo[3,4-b] [1,3,4]thiadiazine-7-carboxylic acid and its salts - Fedotov, S. O.; Hotsulia, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the work was to create a number of organic and inorganic salts of 6-(2,6-dichlorophenyl)-3-(3-methyl-1H-pyrazol-5-yl)-6,7- dihydro-5H-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazine-7-carboxylic acid and study of their properties, as well as selective determination of the biological potential of these compounds. Materials and methods. The synthetic part of the study involved the sequential synthesis of the original compound 4-amino-5-(3- methyl-1H-pyrazol-5-yl)-1,2,4-triazole-3-thiol using a well-established method described in previous articles. The next stage involved the reaction of thiol with 2,3-dichlorobenzaldehyde in a medium of glacial acetic acid. The resulting Schiff base was subsequently reacted with 2-chloroethanoic acid in tetrahydrofuran in the presence of an equimolar amount of sodium hydride. Salts of the corresponding acid were formed during the reaction of 6-(2,6-dichlorophenyl)-3-(3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-5H-[1,2,4] triazolo[3,4-b][1,3,4]thiadiazine-7-carboxylic acid with both organic and inorganic bases in an aqueous-alcohol medium. The structures of all synthesized compounds were determined using 1H NMR spectroscopy and elemental analysis. Additionally, the individuality of each compound was confirmed using high-performance liquid chromatography-mass spectrometry. Мета роботи – створення ряду органічних і неорганічних солей 6-(2,3-дихлорофеніл)-3-(3-метил-1Н-піразол-5-іл)-6,7-дигідро- 5Н-[1,2,4]тріазол-[3,4-b][1,3,4]тіадіазин-7-карбонової кислоти та дослідження їхніх властивостей, а також вибіркове встановлення біологічного потенціалу цих сполук. Матеріали та методи. Реалізація синтетичної частини передбачала поетапний синтез вихідного 4-аміно-5-(3-метил-1H-піразол-5- іл)-1,2,4-тріазол-3-тіолу за відомим методом, що описаний у попередніх статтях. Наступний етап – реакція тіолу з 2,3-дихлорбензальдегідом у середовищі льодяної оцтової кислоти. Одержану основу Шиффа надалі піддавали реакції з 2-хлоретановою кислотою в середовищі тетрагідрофурану за наявності еквімолекулярної кількості натрій гідриду. Солі відповідної кислоти утворювалися в процесі реакції 6-(2,6-дихлорофеніл)-3-(3-метил-1Н-піразол-5-іл)-6,7-дигідро-5Н-[1,2,4]тріазолу-[3,4-b][1,3,4]тіадіазин-7-карбонової кислоти з органічними та неорганічними основами в водно-спиртовому середовищі. За допомогою 1Н ЯМР-спектроскопії та елементного аналізу визначили структуру всіх синтезованих речовин. Метод високоефективної рідинної хромато-мас-спектрометрії підтвердив індивідуальність кожної сполуки.
Синтез і властивості 6-(2,3-дихлорофеніл)-3-(3-метил-1Н-піразол-5-іл)-6,7-дигідро-5Н-[1,2,4]тріазоло[3,4-b][1,3,4]тіадіазин- 7-карбонової кислоти та її солей
Fedotov S. O. - ORCID ID: 0000-0002-0421-5303; Hotsulia A. S. - ORCID ID: 0000-0001-9696-221X.
Keywords: 1,2,4-triazole; pyrazole; properties; in silico research; 1,2,4-тріазол; піразол; властивості; in silico дослідження